KEKUASAAN, KESANTUNAN, DAN SOLIDARITAS DALAM UNGGAH-UNGGUH DI KALANGAN SANTRI OLEH IKATAN ALUMNI FUTUHIYYAH MRANGGEN DEMAK - Hidayatul Rahmi, Fitria Ulfa (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2018)
Speech levels are a linguistic variation to show a different relationship because of the different social status between the speaker and the interlocutor. This research aims to: 1. Explain how the relationship among speech levels, power, politeness, and solidarity in the association of Alumni Futuhiyyah Mranggen, 2. Explain the social or cultural values of the student (santri) in maintaining language speech levels by the association of Alumni Futuhiyyah Mranggen. This is an explanatory descriptive study which is presenting the data by using the referral method or observation. The monitoring and the observations here were carried out by Simak Bebas Libat Cakap (SBLC) method. After that, the data are analyzed by using agih method with advanced technique of replace technique, and pragmatic equivalent method. The results of this research are presented by using formal and informal method. The results of this study indicate the use of various types of speech levels; they are ngoko, madya, and krama by the speakers with different social status. However, this research shows that adherence to a teacher or kyai exceeds the differences on social stratification. These are appropriate with the Islamic boarding house’ (pesantren) concept and terms, namely barokah/berkah, tawadhu’, irsyadul uztad, and murobbi ruhina. The alteration of social status does not affect the use of language politeness’ students and alumni of the Islamic boarding house (pesantren).